2004
DOI: 10.1007/s00285-004-0296-0
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic and stochastic modelling of endosome escape by Staphylococcus aureus: ?quorum? sensing by a single bacterium

Abstract: Deterministic and stochastic models describing quorum sensing by Staphylococcus aureus within an endosome, and the subsequent escape via the production of virulence factors, are developed and analysed. Particular attention is given to a biologically-relevant asymptotic limit of the problem, for which the solutions, including the endosome escape time, can be explicitly characterised in terms of the model parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Production of AI-2 by growing bacteria within mammalian tissues may also serve to control gene expression via self-induction. Related to that hypothesis, it has also been suggested that isolated bacteria may utilize pheromones such as AI-2 to sense the permeability of their surroundings (29,40).…”
Section: Discussionmentioning
confidence: 99%
“…Production of AI-2 by growing bacteria within mammalian tissues may also serve to control gene expression via self-induction. Related to that hypothesis, it has also been suggested that isolated bacteria may utilize pheromones such as AI-2 to sense the permeability of their surroundings (29,40).…”
Section: Discussionmentioning
confidence: 99%
“…swimming, foraging) Tang et al (2007), van Gestel et al (2012) Virulence Pseudomonas aeruginosa Dockery and Keener (2001), Fagerlind et al (2003Fagerlind et al ( , 2005, Viretta and Fussenegger (2004), Netotea et al (2009) AHL, AHQ Koerber et al (2005), Jabbari et al (2010), Gustafsson et al (2004) AIP Escherichia coli Li et al (2006) AI-2, Indole Lee et al (2007) See Taga and Bassler (2003), Miller and Bassler (2001) and West et al (2012) for a more comprehensive list. Note that not all models concentrate on a particular bacterium…”
Section: Hunter Et Al (2013) Ahlmentioning
confidence: 99%
“…. Mathematical models of stall and infected wounds with focus on host tissue degradation by bacteria or quorum-sensing by bacteria have also been considered [12,13,14,15,16,31]. These papers provide complex models expressed as deterministic reaction-diffusion equations that must be solved numerically.…”
Section: Introductionmentioning
confidence: 99%